Integration of fundamental, news and technical analysis on SGX technology stocks - Ho, Brendan Wei Zheng (Nanyang Technological University, 2022)
A recent report by the CNBC reveals that there is increased activity in the US stock market exchange whereby the amount of money transacted in the last five months dated from the report exceeded the previous 12 years combined.[1] This recent trend generally shows that more people are investing. Investment assets (e.g., stocks, bonds) with an objective of generating appreciation profits over a period. This is achieved by applying models which are “Fundamental, Technical and News” analyses in aiding our judgement of an asset. Fundamental analysis (FA) examines asset related economic and financial factors by assessing the asset’s qualitative and quantitative traits to derive its intrinsic value which depicts its underlying value through projected future cash flows. This brings about value investing which aims at trading below this value and employed by famous investor, Warren Buffett.[2] Technical analyses (TA) assess an asset pricing movement in terms of historical data and trade volume. It focuses on determining a price pattern trend to timed entry into or out of the asset. Aiding indicators such as and moving averages computes an ideal predictive model.[3] News analyses (NA) forecasts the impact of social / political news on the global market or share price. An instance includes $1.36 trillion of global stocks wiped off arising from US president then Donald Trump’s tweet on the US – China trade war. [4] Studies have shown from the distribution of literature of which 122 stocks are analyzed, 66%, 23% and 11% are analyzed using technical, fundamental, and combined respectively. Firstly, it counteracts the logical flow of identifying potential assets through its fundamentals followed by performing technical analyses. Secondly, frequency utilization rates of valuation technique for the “discounted free cash flow model” is only at 59%. [5] Lastly, a margin of safety where a substantial percentage of error discount in tabulating the asset’s intrinsic value was not factored in. Thus, the objective of this research is to integrate a logical flow system of incorporating Fundamental, Technical and News analysis on stocks. 16 The research focuses on stocks from the technology sector listed on the SGX stock exchange whereby they will be grouped under different categories of market capitalization and stock pricing. Stocks with low pricing and trade volume between a set time frame from 2015 – 2020 will be eliminated. Next, incorporating the fundamentals assessment of the stocks with emphasis on discounted cash flow analysis and applying a fair margin of safety to determine its intrinsic value. Then, employing technical analysis which deduces an ideal price pattern for value purchase entry into the market. Lastly, news analysis which considers any global economic events that will impact the chosen stocks will be researched upon to determine any correlation between it and stock prices.